Urgency of Mediator (Mediation) in Resolving Divorce Cases in Religious Courts - et. al., Dr. Muhammad Juni Beddu, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This scientific paper was written to investigate the Urgency of Mediators in Resolving Divorce Cases in the Religious Courts. The descriptive method was employed to describe a scientific paper with a theoretical description. It can also be called a grand theory. A mediator is a person who should be able to divert the intention of the two parties from the one who wants to divorce to undo that intention. Therefore, the two parties in the case are settled peacefully. The mediator is the judge himself or an individual or institution that has been certified by the Supreme Court.